Tex19 and Sectm1 concordant molecular phylogenies support co-evolution of both eutherian-specific genes. (December 2015) - Bianchetti, Laurent; Tarabay, Yara; Lecompte, Odile; Stote, Roland; Poch, Olivier; Dejaegere, Annick; Viville, Stéphane
Abstract Background Transposable elements (TE) have attracted much attention since they shape the genome and contribute to species evolution. Organisms have evolved mechanisms to control TE activity. Testis expressed 19 (Tex19) represses TE expression in mouse testis and placenta. In the human and mouse genomes, Tex19 and Secreted and transmembrane 1 (Sectm1) are neighbors but are not homologs. Sectm1 is involved in immunity and its molecular phylogeny is unknown. Methods Using multiple alignments of complete protein sequences (MACS), we inferred Tex19 and Sectm1 molecular phylogenies. Protein conserved regions were identified and folds were predicted. Finally, expression patterns were studied across tissues and species using RNA-seq public data and RT-PCR. Results We present 2 high quality alignments of 58 Tex19 and 58 Sectm1 protein sequences from 48 organisms. First, both genes are eutherian-specific, i.e., exclusively present in mammals except monotremes (platypus) and marsupials. Second, Tex19 and Sectm1 have both duplicated inSciurognathi andBovidae while they have remained as single copy genes in all further placental mammals. Phylogenetic concordance between both genes was significant (p -value < 0.05) and supported co-evolution and functional relationship. At the protein level, Tex19 exhibits 3 conserved regions and 4 invariant cysteines. In particular, a CXXC motif is present in the N-terminal conserved region. Sectm1 exhibits 2 invariant cysteines and an Ig-like domain. Strikingly, Tex19 C-terminal conserved region was lost inHaplorrhini primates while a Sectm1 C-terminal extra domain was acquired. Finally, we have determined that Tex19 and Sectm1 expression levels anti-correlate across the testis of several primates (ρ = −0.72) which supports anti-regulation. Conclusions Tex19 and Sectm1 co-evolution and anti-regulated expressions support a strong functional relationship between both genes. Since Tex19 operates a control on TE and Sectm1 plays a role in immunity, Tex19 might suppress an immune response directed against cells that show TE activity in eutherian reproductive tissues.